Efficient certificateless multi-receiver anonymous signcryption scheme - Yan-lin QIN; Xiao-ping WU; Wei HU (Tongxin xuebao)
To solve the private key escrow problem of identity-based multi-receiver signcryption schemes,the security model for multi-receiver signcryption scheme was constructed,and then a certificateless multi-receiver signcryption scheme based on ECC was proposed.Furthermore,the security of the scheme in the random oracle was based on the computational Diffie-Hellman assumption and elliptic curve discrete logarithm assumption was proved.Meanwhile,the scheme was free from certificate management center and needed no bilinear paring operation in both signcryption and decryption phases.It can also protect both the sender and receivers’identity from leaking out.So the scheme can be applied conveniently to broadcast signcryption in network environment.